2013
DOI: 10.1111/fwb.12135
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between nutrient enrichment, pleurocerid snail density and trematode infection rate in streams

Abstract: Summary Nutrient enrichment is a widespread environmental problem in freshwater ecosystems. Eutrophic conditions caused by nutrient enrichment may result in a higher prevalence of infection by trematode parasites in host populations, due to greater resource availability for the molluscan first intermediate hosts. This study examined relationships among land use, environmental variables indicating eutrophication, population density of the pleurocerid snail, Leptoxis carinata, and trematode infections. Fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Our results, despite the small sample sizes of infected snails, add to previous studies demonstrating that snails can occur in different habitats when parasitized (Williams and Esch ; Jokela and Lively ; Wetzel and Shreve ; Ciparis et al. ). Specifically, large, infected individuals of T. granifera were found in shallower locations than large, noninfected snails.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results, despite the small sample sizes of infected snails, add to previous studies demonstrating that snails can occur in different habitats when parasitized (Williams and Esch ; Jokela and Lively ; Wetzel and Shreve ; Ciparis et al. ). Specifically, large, infected individuals of T. granifera were found in shallower locations than large, noninfected snails.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, our approach (similar to that of Ciparis et al. ) provided a unique opportunity to investigate the biotic interactions between invading snails and their trematode parasites in lotic systems. Furthermore, our results demonstrate that the spatial distributions and habitat associations of invasive thiarid snails are associated with body size and, to a lesser extent, parasite infection.…”
Section: Discussionmentioning
confidence: 99%
“…By investigating both the component and net effects of agrochemicals, we found that the net effect of chlorpyrifos, profenofos, and atrazine is to amplify transmission through the dominance of indirect effects on snail predators and algal dynamics, which are longer lasting than direct effects on snails and schistosome larvae. 10 , 38 By contrast, snail predators appear to be more tolerant to the insecticide malathion, which has trivial net effects on transmission. Similarly, the widely used herbicide glyphosate decreases transmission owing to its reproductive toxicity to snails at environmentally relevant concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have generated DNA sequence data from other life cycle stages, mostly cercariae and metacercariae (Blasco‐Costa & Locke, ; Ciparis, Iwanowicz, & Voshell, ; Karamian et al, ; Locke et al, ; Locke, McLaughlin, & Marcogliese, ); however, the limited sequence data from adult forms prevent accurate species‐ or genus‐level diagnoses of the sequenced life cycle stages. While recent molecular phylogenetic studies (Blasco‐Costa & Locke, ; Hernández‐Mena et al, ; Locke et al, ) have indicated the general position of the Cyathocotylidae among other diplostomoidean families, the very limited number of taxa used in these analyses did not allow exploration of questions of evolution and systematics related to geographic distribution, host associations and environmental switches of the group.…”
Section: Introductionmentioning
confidence: 99%